Application evaluation of virtual reality technology in dental implant training: a new dental implant training system: A CONSORT-compliant trial. Issue 39 (1st October 2021) - Zhou, Yong; Chen, Wanlu; Zhao, Xiaoxian; He, Bingwei; Huang, Wenxiu; Wu, Dong; Chen, Jiang
Abstract : Abstract: To evaluate the application of virtual reality technology in a dental implant training system. A 3-dimensional model of mandible was established by Mimics17.0 software based on the Digital Imaging and Communications in Medicine data obtained from cone beam computed tomography scanning of the patient in mandibular. Thirty physicians were divided into 2 groups. The virtual reality dental implant training system was used for group A, while conventional theoretical knowledge training and clinical demonstration were performed in group B. All young physicians have a 1-month study. After training, all the physicians in groups A and B would conduct a questionnaire survey according to the training situation, which was compared between the 2 groups. The success rate of the operation was also evaluated and compared. The median scores in the 5 dimensions of postoperative assessment of group A was 9/9/9/8/8, and of group B was 6/7/6/7/7. The scores of the 5 dimensions were significantly higher than those of group B ( P < .05), indicating that group A has a better grasp of the simulator. After the training of simulated mandibular implants in group A, the deviations in the 4 dimensions of mesiodistal, buccal and tongue, depth, and angle were significantly lower than those of group B ( P < .05). Group A has smaller deviations in each of the 4 dimensions than those in group B, indicating group A has a higher operation success rate. We independently develop a set of virtual surgery system for dental implant training, which can be used for teaching and training, with good operability and predictability, to achieve a breakthrough in dental implant surgery training.